Bilateral distal transradial access for subclavian artery stenosis intervention - Chen, Lin; Chen, Xiaofang; Sun, Mingchen; Naing, Toe Wai Wai; Li, Zhaokai; Lai, Min; Tian, Zixin; Cheng, Ye; Kang, Huiyuan; Wang, Yan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundConventionally, subclavian stenting has been performed via the femoral artery, but this approach is associated with complications such as bleeding, patient discomfort, and prolonged recovery. The transradial artery access (TRA) has gained popularity due to its lower vascular complication rates, though it carries a risk of radial artery occlusion (RAO). The distal transradial access (dTRA) has emerged as an alternative with lower occlusion rates.ObjectiveThis study aimed to assess the safety and technical feasibility of bilateral distal transradial access for percutaneous interventions in subclavian artery stenosis.MethodsWe present 10 cases of subclavian artery stenosis, in whom diagnostic angiography was performed by SIM2 catheter via the contralateral side access. Ipsilateral side distal radial artery was subsequently accessed for balloon-expandable stents delivery.ResultsAmong the 10 patients, 9 were male and 1 was female, with a mean age of 65.8 years. The systolic pressure difference between the left and right arms was 21.00 mmHg. Among them, 2 cases had 80% stenosis, 2 cases had total occlusive lesions, and 6 cases had 90% stenosis. 1 case had right subclavian artery stenosis, while 9 cases had left subclavian artery stenosis. The results showed a 100% success rate for bilateral distal radial artery puncture and a 100% completion rate for subclavian stenosis intervention procedures. No RAO or subclavian artery restenosis was observed during the 1-month follow-up.ConclusionIn patients with subclavian stenosis bilateral dTRA is a safe and minimally invasive method for patients and ergonomically comfortable for operators.